Assassinatos de mulheres: um estudo sobre a alegação, ainda aceita, da legítima defesa da honra nos julgamentos em Minas Gerais do ano 2000 a 2008 - Margarita Danielle Ramos (2010)
This work uses a gender perspective to analyse the discourse in six documents from Brazilian jurisprudence in the jurisprudence of Minas Gerais. The objective is to undersatand how lawyers appeal until the present date to the legitimate defence of honour in trials of men who have killed a woman in order to avoid punishment for their crime. The analysis is based on two sets of studies: the study of the legislation concerning the concept of honour since the colonial period in Brazil and the study of the struggle that the Brazilian feminist movement has undertakento remove violence against women from the private sphere and turn it into gender violence. The work attempts to show that the murder of women is the final step in a chain of violations against women, which begins in the devalued way that women are produced in discourse.